2018
DOI: 10.1083/jcb.201712117
|View full text |Cite
|
Sign up to set email alerts
|

SPATA7 maintains a novel photoreceptor-specific zone in the distal connecting cilium

Abstract: Photoreceptor-specific ciliopathies often affect a structure that is considered functionally homologous to the ciliary transition zone (TZ) called the connecting cilium (CC). However, it is unclear how mutations in certain ciliary genes disrupt the photoreceptor CC without impacting the primary cilia systemically. By applying stochastic optical reconstruction microscopy technology in different genetic models, we show that the CC can be partitioned into two regions: the proximal CC (PCC), which is homologous to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 48 publications
2
58
2
Order By: Relevance
“…These results are surprising, given suggestions that CEP290 is essential for ciliogenesis and proposals that it plays a major role in localizing NPHP5 and other transition zone proteins (32,51,67,68). They are in stark contrast to those obtained for another LCA-associated protein, SPATA7, deficiencies in which we recently reported to cause drastic redistribution of CC proteins, including CEP290 (35). The idea that CEP290 is essential for ciliogenesis in the retina may have arisen from failure to look at early timepoints in the development of the CC as we have done in this study.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…These results are surprising, given suggestions that CEP290 is essential for ciliogenesis and proposals that it plays a major role in localizing NPHP5 and other transition zone proteins (32,51,67,68). They are in stark contrast to those obtained for another LCA-associated protein, SPATA7, deficiencies in which we recently reported to cause drastic redistribution of CC proteins, including CEP290 (35). The idea that CEP290 is essential for ciliogenesis in the retina may have arisen from failure to look at early timepoints in the development of the CC as we have done in this study.…”
Section: Discussioncontrasting
confidence: 78%
“…It has recently been proposed that retina-specific ciliopathies can arise from defects in retina-specific structures or aberrations in spatial distributions of components within the sensory cilia (outer segments plus CC) of rods and cones. In a recent study using methods similar to those employed here, we observed that a number of ciliary components, including CEP290, undergo photoreceptor-specific re-distribution in the absence of the product of another LCA-associated gene, Spata7 (35). These results and the spectrum of .…”
Section: Introductionsupporting
confidence: 67%
“…However, it is known that transition zone assembly is highly cell-type specific, and Rpgrip1l plays a key role in this process (Wiegering et al, 2018). Extension of Rpgrip1l further beyond the distal appendages in this cell line is reminiscent of RPGR1P1L localisation in photoreceptors in vivo , where it is localised along the connecting cilium (Dharmat et al, 2018).…”
Section: Resultsmentioning
confidence: 91%
“…Whereas primary cilia are important throughout the body, rod cell degeneration in ciliopathies likely reflects both general and photoreceptor-specific functions of cilium components (46). Combining cryo-ET and superresolution fluorescence nanoscopies have allowed us to map the repeating structures and localization of protein targets with nanoscale precision in the rod sensory cilium.…”
Section: Discussionmentioning
confidence: 99%